2014
DOI: 10.1073/pnas.1417419112
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor-mediated Lon proteolysis restrictsBacillus subtilishyperflagellation

Abstract: The Lon AAA+ protease is a highly conserved intracellular protease that is considered an anticancer target in eukaryotic cells and a crucial virulence regulator in bacteria. Lon degrades both damaged, misfolded proteins and specific native regulators, but how Lon discriminates among a large pool of candidate targets remains unclear. Here we report that Bacillus subtilis LonA specifically degrades the master regulator of flagellar biosynthesis SwrA governed by the adaptor protein swarming motility inhibitor A (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 55 publications
3
91
0
Order By: Relevance
“…possesses no SwrA homolog, DegS may be required to produce enough DegUϳP to bind and activate the fla-che operon promoter in Paenibacillus sp. Thus, induction of flagellar genes is mainly controlled by SwrA levels in B. subtilis (12), whereas it may be controlled by DegUϳP levels in Paenibacillus sp. surface structures directly contact the external environment, the WsfP-and PBN151_4312-related regulations are expected to play important roles under surface growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…possesses no SwrA homolog, DegS may be required to produce enough DegUϳP to bind and activate the fla-che operon promoter in Paenibacillus sp. Thus, induction of flagellar genes is mainly controlled by SwrA levels in B. subtilis (12), whereas it may be controlled by DegUϳP levels in Paenibacillus sp. surface structures directly contact the external environment, the WsfP-and PBN151_4312-related regulations are expected to play important roles under surface growth conditions.…”
Section: Resultsmentioning
confidence: 99%
“…SwrA is the master swarming regulator that accumulates following surface contact. This SwrA accumulation results from a lack of proteolysis by the LonA AAAϩ protease/SmiA adaptor (98). While the exact mechanism that relieves proteolysis of SwrA is under investigation (D. Kearns, unpublished data), this surface contact-controlled transcription regulation allows differentiation into swarmer cells.…”
Section: Surface Sensing and Signal Transductionmentioning
confidence: 99%
“…It was further shown that LonA-mediated degradation of SwrA happens only in the presence of swarming motility inhibitor A (SmiA). SwrA mutants that were resistant to proteolysis and caused hyperswarming were identified; it was speculated that these mutated residues were required for SmiA interaction (8). Gerard Wong (UCLA, Los Angeles, CA) presented his collaboration with George O'Toole with a surprising finding on surface sensing in Pseudomonas aeruginosa PA14.…”
Section: Bacterial Adhesion Factors and The Planktonic To Biofilm Lifmentioning
confidence: 99%